Reliability evaluation of machines based on their operation risks - Igor A. Khozyaev; Leonid V. Koledov; Vladislav A Vazhenin (Advanced Engineering Research, 2016)
The work objective is to develop a technique of evaluation and forecasting of the complex systems reliability based on the statistic simulation of their operation. A method of risks inherent in the lost benefit is used. Dependences for determining failure losses under the system operation according to the degree of its reliability are offered. A simulation program taking into account risks of reliability - “Reliabilify” - is worked out. The developed method verification is based on the performance simulation of the feed ingredient cutter, such as U17-UKI. The results obtained reflect real processes occurring in the course of the technical objects operation. The method is fully formalized and can be used for estimating the reliability of any engineering system.